Erratum: Computer Training of Rural Central American Teachers: Opportunities and Challenges - JIAEE Editors (Journal of International Agricultural and Extension Education, 2024)
Correction: The DOI of the article "McDermott, M. R., Murphrey, T. P., & Wingenbach, G. (2013). Computer Training of Rural Central American Teachers: Opportunities and Challenges. Journal of International Agricultural and Extension Education, 20(3), 21-32” was incorrect as published. The correct DOI is: 10.4148/2831-5960.1435